His Brother's Blood : The Last (Unfinished) Novel - Hornung, E. W. (Ernest William), 1866-1921 (1880-1920 British authors series, 2015)
At the turn of the nineteenth century into the twentieth, hearts would have beat a little faster with word of a new novel by E. W. Hornung, one of the most widely read writers of the time, a born story-teller with an abundance of plots and, invariably, a trick up his sleeve. His A. J. Raffles stories rivaled Conan Doyle's Sherlock Cover His Brother's BloodHolmes in popularity. That new novel is His Brother s Blood, a Cain and Abel tale with a different cast of light. It took shape during the fifteen months preceding his death. Hornung believed it would out-do all his other novels. Sadly, he died too soon to complete the task. With permission of the Hornung family, Hornung s biographer Peter Rowland has transcribed the 20,000-word manuscript, the six exciting chapters, housed in Cadbury Research Library, University of Birmingham. He also includes an Introduction and an Afterword. It offers convincing details on how the plot may have been intended to develop and come to a surprising resolution. In the Internet age nearly all of Hornung s fiction is available. Once again general readers and critics are interested in this stylish, sensitive writer. They will find His Brother s Blood: The Last (Unfinished) Novel a great read, every bit Hornung.